Perilaku Auditor dalam Situasi Konflik Audit: Peran Locus of Control, Komitmen Profesi dan Kesadaran Etis - Umi Muawanah; Nur Indriantoro (The Indonesian Journal of Accounting Research, 2013)
In general, the objective of this study  was to determine the interaction effects of personality  variables and cognitive style on the behavior of auditor in an audit conflict situation. In particular, this study examined the moderating effect of ethical awareness on relationship between locus of control as well as professional commitment and auditors’ response in an audit conflict situation i.e. auditors’ ability to resist or to accede clients’ presures. The study used data collected through mail survey from seventy five experienced auditors from a sample of CPA firms. The questionaire list  sent to each respondent was designed to provide data on four variables: locuc of control, professional commitment, ethical awareness, and auditors’ response in an audit conflict situation. The data were analysed using multiple regression technique.The analysis found that ethical awareness moderated the relationship between personality variables (i.e. locus of control and professional commitment) and auditors’ response in an audit conflict situation. These finding supported the previous research results and literature of behavioral accounting arguing that the interaction between personality variable and cognitive style affect the behavior in decision making, included ethical decision making.Result of this study implied that the explicit recognition of both personality variables (i.e. locus of control and professional commitment) and ethical awareness as cognitive style variable provides a better explanation for audit practice in an auditors’ ethical decision making. Other implications for audit practice were also considered. In addition, to understand the result and implication, constrain and limitations of this study should be carefully though about and for this reason, the study also proposes the directions for future research in the area.